Rosa canina Extract has Antiproliferative and Proapoptotic Effects on Human Lung and Prostate Cancer Cells. (17th February 2020) - Kilinc, Kagan; Demir, Selim; Turan, Ibrahim; Mentese, Ahmet; Orem, Asim; Sonmez, Mehmet; Aliyazicioglu, Yuksel
Abstract: Although several studies have investigated the cytotoxic effects of different Rosa species, there has been only limited research into the cytotoxic effect of Rosa canina. The purpose of this research was to evaluate the antioxidant properties, phenolic characterization, and cytotoxic effects of R. canina on human lung (A549) and prostate (PC-3) cancer cells and the possible mechanisms involved. The antioxidant properties and phenolic characterization of the extract were determined using spectrophotometric methods and RP-HPLC, respectively. The cytotoxic activity of the extract was determined using the MTT assay. The mechanism involved in the extract's cytotoxic effect was then evaluated in terms of apoptosis, the cell cycle, mitochondrial membrane potential (MMP), and caspase activity using fluorometric and luminometric methods. The TPC value of the extract was 58.97 ± 2.22 mg gallic acid equivalents per gram sample, and ascorbic acid and p -coumaric acid were detected as major phenolics in the extract. R. canina extract exhibited a selective cytotoxic effect on A549 and PC-3 cells compared to normal fibroblast cells. The extract induced cell cycle arrest at the G1 phase and apoptosis via reduced MMP and increased caspase activity in these cells. Phytomedical applications of R. canina may represent promising approaches in the treatment of cancer.